Acculturation, adolescent mental health & youth suicide in modern Ireland - Smyth, Caroline (Trinity College (Dublin, Ireland). School of Psychology, 2004)
Since 1990, Ireland has witnessed a 400% increase in young, male suicide (Beagley, 1999) such that Ireland ranks 24th internationally in terms of its youth suicide rate (WHO, 2002) and 25th highest of 35 countries across Europe (Lyddy, 2004) however, more dramatic than the overall rate of suicide, is Ireland's top ranking in terms of the gender ratio of completed suicides where, for 2001, 4.7 male suicides were seen for every 1 female suicide. This increase in suicide has been seen at a time of extensive social and cultural change where a clear move away from "traditional" Irish values towards "Celtic Tiger" Ireland has been seen. Patterns of modernization, globalization and secularization have been noted to take effect across every sector of society. Despite the general suggestion that this sociocultural redesign may be linked to the increase in suicide, both research and clinical investigations of adolescent mental health and youth suicide have, in the main, continued to fail to include social and cultural factors resulting in a dearth of information. Marking a departure from previous investigations, this research specifically took a contextualised, culturally embedded approach to the issue of youth suicide.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin